ANALYSIS OF STUDENTS' CREATIVE THINKING ABILITIES USING MIND MAPPING LEARNING METHOD IN HISTORY SUBJECT AT SENIOR HIGH SCHOOL: Analisis Kemampuan Berpikir Kreatif Siswa Menggunakan Metode Pembelajaran Mind mapping Pada Mata Pelajaran Sejarah di SMA - Nidaan Chofiyya; Aulia Fitriany; M Khusni Mubarok (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to understand students' how capability to generate creative ideas through the use of mind mapping method compares to conventional method. The research is aiamed at achieving specific objecktives, as follows: 1) To know the planning in history learning using the mind mapping method, 2) To understand the implementation of mind mapping techniques in history lessons, 3) To assess the outcomes of the mind mapping technique during the history learning process. The present research method uses a qualitative approach which results in descriptive information in the form of communication in the form of speech or text from individuals or behaviors that are observable. Based on the findings of the study, implementation of the mind mapping techniques has been proven to effectively support students' creative thinking skills, as well as making the learning process more active and less monotonous compared to conventional teaching methods. Additionally, the he implementation of mind mapping witten history education has a positive impact and has theability to significantly encouraging the improvement of learners creative thinking skills.